Coronary Stenosis in Type 2 Diabetes: A Comparative Review of HbA1c, Lipid Profiles, Blood Pressure, and BMI - Shivankan KAKKAR; Monica JAIN; Jaya DADHICH; Ayesha ARORA; Nivedita GUPTA; Jitendra Kumar GUPTA (Modern Medicine)
Coronary artery disease (CAD) remains a leading cause of morbidity and mortality globally, with Type 2 Diabetes Mellitus (T2DM) significantly exacerbating its progression and severity. Understanding the interplay between modifiable risk factors and the degree of coronary stenosis in T2DM patients is crucial for optimized patient management and risk stratification. This review article critically evaluates the existing literature comparing the association of HbA1c, triglycerides, HDL cholesterol, blood pressure, and body mass index (BMI) with the degree of coronary stenosis in individuals with T2DM undergoing coronary angiography. We explore the pathophysiological mechanisms linking these factors to atherosclerosis and stenosis, analyze the evidence from observational and interventional studies, and discuss the relative strength and limitations of each marker in predicting and managing coronary stenosis in this high-risk population. Ultimately, this review aims to provide medical professionals with a comprehensive and nuanced understanding to guide clinical decision-making in the prevention and treatment of CAD in T2DM patients.